2020
DOI: 10.1101/2020.05.11.085670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RNase J-based RNA degradosome is compartmentalized in the gastric pathogenHelicobacter pylori

Abstract: Importance 46Helicobacter pylori is a bacterial pathogen that chronically colonizes the stomach of 47 half of the human population worldwide. Infection by H. pylori can lead to the 48 development of gastric pathologies such as ulcers and adenocarcinoma, that causes 49 up to 800.000 deaths in the world each year. Persistent colonization by H. pylori relies 50 on regulation of the expression of adaptation-related genes. One major level of such 51 control is post-transcriptional regulation that, in H. pylori, lar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Fractionation and Immunoblotting. H. pylori fractionation was performed as in Tejada-Arranz et al (57). H. pylori strains were grown in the absence or presence of 1 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…Fractionation and Immunoblotting. H. pylori fractionation was performed as in Tejada-Arranz et al (57). H. pylori strains were grown in the absence or presence of 1 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…pylori to obtain crystals were unsuccessful. As we previously reported (Tejada-Arranz et al, 2020b), the N-terminal part of RNase J (first 120 amino acids) that is specific of the Helicobacter species is predicted to be an intrinsically disordered region (IDR). After truncating this region, well diffracting crystals were obtained from this RNase J form comprising residues 137-691 (from H. pylori strain 26695, uniprot P56185).…”
Section: Structure Of the H Pylori Rnase Jmentioning
confidence: 86%
“…RhpA is the sole DEAD-box RNA helicase encoded by the H. pylori genome and is essential for colonization in the mouse infection model (El Mortaji et al, 2018). Furthermore, we recently demonstrated that, in H. pylori , the RNA degradosome is compartmentalized into clusters at the inner membrane whose formation is regulated and likely represents a major level of control of its activity (Tejada-Arranz et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation